MERANTAU PADA ORANG WANCI - Irwanuddin Irwanuddin; Nasruddin Suyuti; Hasniah Hasniah (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
This study aims to find out the reason for the Wanci in Wandoka Village to migrate and describe the economic life of the nomads' families before migrating and after migrating. Data collection techniques are taken through observation (observation) and in-depth interviews (in-depth interviews). Data analysis was carried out descriptive qualitative. The results of the study show that the reason for the Wanci going to wander is due to two main factors, namely (1) the natural condition (geographical) and the topography of the land / land that is not so fertile as agricultural land; (2) family economic factors, where people feel they cannot depend on farming and fishing activities; (3) employment that is relatively very rare; (4) educational factors; and (5) psychological factors. Keywords: family of wander, Wanci’s people